Hubungan Antara Motivasi Berprestasi dan Self-Efficacy dengan Keterampilan Bermain Atlet Tenis Meja Klub di Kota Cimahi - Lanny Yuniar; Yusuf Hidayat; Riansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the simultaneous relationship between achievement motivation and self-efficacy on the playing skills of table tennis club athletes in Cimahi City. The research method used a quantitative approach with a descriptive-correlational design. The study subjects consisted of 30 active table tennis athletes who are members of table tennis clubs in the city of Cimahi. The instruments used were questionnaires designed based on the theories of each variable—achievement motivation and self-efficacy—while the instrument for measuring table tennis playing skills was the Game Performance Assessment Instrument (GPAI). The results of the study indicate that the variables of achievement motivation and self-efficacy simultaneously have a significant effect on playing skills, with a significance value of 0.000 < α 0.05. Partially, the results show that the achievement motivation variable has a positive and significant effect on table tennis playing skills, and the self-efficacy variable also has a positive and significant effect on table tennis playing skills. In conclusion, achievement motivation and self-efficacy have a positive and significant effect on the playing skills of table tennis athletes in Cimahi City. Keywords: Playing Skills, Achievement Motivation, Self-Efficacy